A LOOK INSIDE COOPERATION BETWEEN PROSECUTORS AND LAW ENFORCEMENT DURING CRIME SCENE INVESTIGATION - Dževad Mahmutović; Berina Huskanović (Human Research in Rehabilitation, 2017)
The paper deals with crime scene investigation as a measure of inquiry, conceptually and substantially, subjects of investigation, as well as their mutual relations. The analysis of the existing legal framework suggests that the current Criminal Procedure Code of Bosnia and Herzegovina offers the appropriate basis for the cooperation between prosecutors and law enforcement. However, previous practice indicates certain shortcomings in the cooperation and coordination between prosecutors and law enforcement. With this paper, the authors wanted to examine the opinions of direct actors on this matter. The results show that they are satisfied with the legal regulation of their mutual relations during investigations, and they express positive opinions in terms of their cooperation. Of course, the possibility of improving that cooperation is also noted, and the methods of achieving it should be identified in further research.